PENINGKATAN PANGSA PASAR PERUASHAAN E-COMERCE MELAUI CUSTOMER LOYALTY - Limous, Celine; Sutrisno, Nuno (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study was to determine the effect of Social Media Marketing Activities through Value Equity, Brand Equity, and Relationship Equity, on Customer Loyalty on customers of the Zalora Indonesia e-commerce site in Jakarta. The research method used in this research is through a survey. Data analysis was carried out quantitatively and used a causal research design. The sampling method used in this research is to use Non-Probability Sampling with Purposive Sampling technique. The total sample used in this study was 297 respondents. The data analysis technique used in this research is Structural Equation Modeling (SEM). The results of this study indicate that Social Media Marketing Activities through Value Equity, Brand Equity, and Relationship Equity have a significant influence on Customer Loyalty. This research is expected to provide input or advice to e-commerce companies, especially Zalora Indonesia, which is the object of this study how to increase the Brand Loyalty of its consumers, because it can have an impact on increasing the market share of e-commerce companies in Indonesia.